(untitled) (CAHIERS MAGELLANES-NS, 2024)
Translation plays a significant role since it broadens the audience for varied literary landscapes to include readers worldwide. India is home to a wide spectrum of languages and civilizations from all around the world. By translating cultural representations from regional languages into widely recognized languages, such as English, French, Spanish and others one can achieve the goal of bringing together a variety of cultural representations. Writers can often break out from the confines of a particular language and explore the vast domain of Indian literature when they choose this approach. By translating their works, authors can reach readers worldwide. Through the dissemination of Indian narratives to readers all over the world, Indian literature helps to cultivate cultural links and encourages global unity. There is a long and illustrious literary heritage in India's regional languages. The translation of works from languages that have a small readership is done to preserve those texts and make them accessible to a larger audience. The preservation of historical relics and the preservation of literary works of great value are both aided by this. Every single one of India's multiple languages and dialects has its own distinct and significant literary, oral, folk, and narrative heritage. By providing a forum in which authors from lesser-read and spoken Indian languages can have their voices heard and appreciated on a larger scale, translation contributes to the promotion of a more inclusive representation of Indian literature. To the benefit of authors, critics, and readers alike, a healthy literary interchange that is facilitated by translation can be advantageous. It gives Indian authors a platform from which they may interact with literary trends, ideas, and perspectives from around the world, which ultimately contributes to an improvement in the quality of literature on a larger scale.